(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The objective is to assess the antibiotic resistance rate in the treatment of pneumonia and investigate the drug-resistant gene characteristics of Gram-negative bacteria in pneumonia cases among children aged 2 to 24 months with a history of prematurity, hospitalized for pneumonia in the Respiratory Department of Children’s Hospital 1, using nasal tracheal aspirate (NTA) samples for PCR and drug-resistant gene detection. Method: This is a prospective, cross-sectional descriptive study with analysis of 120 cases of community-acquired pneumonia (CAP) requiring hospitalization, treated in the Respiratory of Children’s Hospital 1 from September 2023 to July 2024. Nasal tracheal aspirate (NTA) samples were collected and subjected to multi-pathogen PCR for lower respiratory tract infections. Results: Between September 2023 and July 2024, 120 cases meeting the criteria were included in the study. The findings showed the following: Prematurity levels: < 28 weeks: 10.0%, 28–32 weeks: 22.5%, > 32 weeks: 67.5%. Nutritional status: Overweight: 3.2%, normal or mildly malnourished: 76%, moderately malnourished: 10%, severely malnourished: 10.8%. Bacterial pathogens detected from NTA cultures:Streptococcus pneumoniaewas the most common pathogen, accounting for 26.5%, and Escherichia coli (17.6%) both carried the ESBL and AmpC resistance genes. There were 3 cases with positive cultures for Haemophilus influenzae non-type B.Antibiotic resistance: Over 50% of S. pneumoniae strains were resistant to Penicillin and Clarithromycin; 66.7% were resistant to Cefotaxime, and 44.4% to Ceftriaxone and Clindamycin. Two cases of S. pneumoniae were resistant to Levofloxacin.Gram-negative bacteria antibiotic resistance genes detected: AmpC resistance genes: DHA (9/32), ACC (2/32), FOX (1/32), Colistin resistance genes: mcr3 (4/32), mcr4 (4/32), mcr5 (6/32), mcr9 (3/32), mcr10 (2/32), ACarbapenemase genes: OXA48 (2/32), OXA51 (5/32), OXA58 (2/32), IMP (6/32), VIM (2/32), NDM1 (6/32), GES (3/32), KPC (1/32). Conclusion: Necessitating close monitoring of resistance to select appropriate antibiotics. Enhanced surveillance and monitoring of drug resistance in both hospitals and communities are essential for timely adjustments in treatment regimens. Infection control measures, such as hand hygiene, surface disinfection, and the use of isolation techniques, are critical in preventing the spread of drug-resistant bacteria.